Invasive Group B Streptococcal Disease in Two Pediatric Patients with Systemic Lupus Erythematosus. (4th April 2013) - Wu, Dongning; Bromberg, Kenneth; Jodorkovsky, Roberto
Abstract : Systemic lupus erythematosus (SLE) is an autoimmune disease associated with high morbidity and mortality, often caused by infection. We report two patients with SLE who were treated with steroids and immunosuppressive medication and then developed invasive Group B Streptococcus (GBS) infections. While GBS infection is rare in the nonneonatal pediatric age group, GBS should be considered when treating SLE patients presenting with signs of infection.